2008
DOI: 10.1080/09540120701583761
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with health services for STIs, HIV, AIDS among a high-risk population in West Africa

Abstract: The goal of this study was to develop an instrument and assess the degree of satisfaction regarding HIV/STIs services for women working in, associated with, or living in or nearby, prostitution environments. This study took place in seven West-African countries (Benin, Burkina Faso, Ghana, Mali, Niger, Senegal, Togo) participating in the West Africa Aids Program (AIDS3). A validated six-dimension questionnaire was used to interview 698 women. The main inclusion criterion was having had recourse to adapted serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The West African Project to Combat AIDS and STIs provided preventive and curative care to FSWs and their clients in nine West African countries, with funding from the Canadian International Development Agency [24]. Coordination of services along several major transport routes was also noted [25-29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The West African Project to Combat AIDS and STIs provided preventive and curative care to FSWs and their clients in nine West African countries, with funding from the Canadian International Development Agency [24]. Coordination of services along several major transport routes was also noted [25-29].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, innovative approaches to education activities were employed by projects in Cote d’Ivoire and along the West African highways; these activities included promoting condom use through picture albums, videos, cue cards, drawings, billboards, radio, calendars, t-shirts, and commercials. Advertisements in these projects were localized to reduce project costs [24,44]. In Malawi, nightclub disk jockeys promoted condom use and distributed safe sex messages [45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include use of night clinics [33] or taking STI treatment directly to sex workers and clients in venues such as hotels [57]. Peer educators have also been deployed to raise awareness about STIs, promote STI services, reinforce correct use of STI medications, and facilitate follow-up visits and partner education and treatment [21,58]. A cross-sectional study in Abidjan, Côte d'Ivoire, at 29 health care facilities and 10 pharmacies found that perceptions of low quality or stigmatising attitudes in the public sector meant that many FSWs preferred accessing private providers or pharmacists for STI treatment.…”
Section: Resultsmentioning
confidence: 99%
“…First, a systematic review of the English literature identified from PubMed searches was conducted to explore candidate measure items of patient satisfaction with HIV/AIDS care and treatment services [11], [17], [20], [23][28]. We found a number of instruments, which were applied in both developed and developing countries.…”
Section: Methodsmentioning
confidence: 99%